Using Interface Design to Develop Computational Thinking Skills - Tom Crick (Proceedings of 10th Workshop in Primary and Secondary Computing Education, 2015)
Human-computer interaction is a long established sub-discipline of computer science. While there has been significant focus on the importance of developing computational thinking skills, there appears to be a gap in the literature in using HCI principles, analysis and design as a framework for doing so. We present the first step to identify methodologies for systematically introducing HCI to pupils from an early age, presenting a commentary for their prospective future application, comparing to similar approach as other foundational aspects of computer science in developing computational thinking skills that have been considered for the past decade.